Design The Business Model For Mie Ayam Bakso Sarangan Using The Business Model Canvas Approach - Fauzi, Akmal; Praptono, Budi; Pulungan, Muhammad Almaududi (eProceedings of Engineering, 2025)
Abstract— Mie Ayam Bakso Sarangan, a culinary businessfrom Bekasi specializing in chicken noodles and handmademeatballs, has been operating for over three years. However, ithas recently faced a steady decline in sales and revenue due toseveral challenges: a lack of sales system optimization,insufficient marketing efforts, inadequate procurement ofsupporting facilities, changes in the business environment, andincreased competition in the same field. To address theseissues, a comprehensive evaluation of the business model isessential, leading to the design of a new, more effectivebusiness strategy using the Business Model Canvas (BMC)method. The proposed redesign will begin by gathering keydata from various sources. The current business model will beassessed through interviews and observations with the owner,allowing us to map the nine blocks of the BMC. In addition,customer profiles will be developed through market segmentsurveys to better understand consumer behavior andpreferences. Information on the business environment will becollected through online research and literature studies. ASWOT analysis will then be conducted to identify strengths,weaknesses, opportunities, and threats, guiding theformulation of a strategic plan for improvement. From theseinsights, a new BMC will be designed, introducing innovationsand enhancements to each block. This approach aims torevitalize Mie Ayam Bakso Sarangan's operations, ensuring itscompetitiveness in the market and driving business growth. Keywords— BMC, Value Proposition, SWOT, MSMEs, MieAyam Bakso Sarangan